Non-Labor Input Quality and Small Farms in Sub-Saharan Africa : A Review - Michelson, Hope; Gourlay, Sydney; Wollburg, Philip (World Bank, Washington, DC, 2022)
Adoption of non-labor agricultural inputs, including pesticides and mineral fertilizers, remains low among small-scale farmers in many low-income countries. Accurate measurement of the quality of these inputs and of quantities deployed is essential for assessing economic returns, understanding the drivers of agricultural productivity, and proposing and evaluating policies for increasing agricultural production. Reviewing evidence regarding the quality of mineral fertilizers and pesticides available to small farmers in Sub-Saharan Africa, this paper summarizes four key findings. First, the available evidence on non-labor input quality to date centers mostly on urea fertilizer and glyphosate herbicide, with limited assessment of other important inputs, including multi-nutrient fertilizers. Second, the evidence shows that nitrogen shortages are exceedingly rare for urea, although quality problems are more common in fertilizer blends including nitrogen, phosphorous, and potassium blends, as well as diammonium phosphate, and in glyphosate herbicide. Third, although nutrient shortages in nitrogen, phosphorous, and potassium fertilizer blends and diammonium phosphate fertilizer blends are likely attributable to problems with manufacturing and storage, problems with available herbicides could be due to manufacturing issues, counterfeiting, or adulteration. Fourth, although farmers are broadly suspicious of the quality of mineral fertilizer and pesticides, evidence from several studies suggests that these beliefs do not reflect lab-based assessments of quality. In light of these findings, this paper recommends best practices for evaluation of non-labor input quality and summarizes research evaluating farmer assessment of fertilizer and pesticide quality. The paper concludes by identifying key evidentiary gaps related to measuring non-labor agricultural input quality and use, and recommends specific topics for future research.